High Frequency Characteristic Of Rogowski Coil - Ping Li; Tao Liang; Yangchun Cheng; Liang Zhao (Institute of Advanced Engineering and Science, 2012)
According to the transfer impedance getting from distributed parameter model,we analyse the influences of magnetic conductivity ，the number of turns ,capacitance to the shield and interturn capacitance on the high frequency characteristic of Rogowski coil through theories and simulations. Simulation shows that there are a series of zeros in high frequency band, but on the whole, the high frequency response does not change with the increase of frequency. The magnetic conductivity, number of turns and capacitance to the shield can influence the frequency at which zero appears, but the high frequency characteristic of Rogowski coil can’t be influenced. Considering the interturn capacitance, the curve of high-frequency response characteristic presents a